METODE BERCERITA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X MA MIFTAHUL MIDAD LUMAJANG TAHUN AKADEMIK 2023/2024 - Diyah Mahmawati; Syafi’atul Mubayyinah (Mastery: Master of English Language Journal, 2024)
This research was conducted because of the low level of English speaking skills which is caused by the lack of learning methods used to support English lessons with an average that is still below, it is still in 60, while the KKM set for English subjects is 75. This research aims to determine the effect of storytelling methods on speaking skills among groups of students taught using the method of storytelling for class X students of MA Miftahul Midad Lumajang Regency East Java in the academic year 2023/2024. This research is a classroom action research. The population in this study was 30 students. Class X students of MA Miftahul Midad Lumajang Regency, academic year 2023/2024. The sample for this research consisted of 30 students. The data collection method used ia a direct observation techniques that assisted with a rubric for assessing English speaking skills. Further, the data that has been collected is analyzed using analytical techniques descriptive statistics and inferential statistical analysis (t-test). The results of this research show that there is a significant influence of storytelling methods on English speaking skills among the group of students studied with the storytelling method.